Deny Practices in Immigration in the Prevention of Terrorism (Law Research Review Quarterly, 2017)
Immigration control through the block system is part of the implementation of the duties and functions of the Directorate General of Immigration as a state agency that carries out government affairs in the areas of immigration, law enforcement, state security and facilitators of community welfare development, which have not been fully empowered for law enforcement functions outside of immigration interests. Formally the immigration blocking system has openness to cross-sector cooperation for its use. In the context of preventing terrorism, immigration control based on a banned system has concepts and facilities that can be a means to strengthen the carrying capacity of the implementation of terrorism prevention in Indonesia while still paying attention to the human rights side.